Pemberdayaan Masyarakat melalui Produksi Gula Aren di Desa Rannaloe Kecamatan Bungaya Kabupaten Gowa - Husniah,; Hasaruddin,; Sahib, Muzdalifah (Jurnal Berita Sosial, 2025)
The main problem in this study is how to empower the community through palm sugar production in Rannaloe Village, Bungaya District, Gowa Regency? The sub-problems in this study are: First, the stages of community empowerment in making palm sugar in Rannaloe Village, Bungaya District, Gowa Regency? Second, economic improvement in palm sugar production in Rannaloe Village, Bungaya District, Gowa Regency. This study uses a qualitative research method. The data collection techniques used are through interviews, documentation and direct observation in Rannaloe Village, Bungaya District, Gowa Regency. The data sources for this study are secondary and primary data. The results of the study show that: First, the stages of community empowerment in making palm sugar in Rannaloe Village, Bungaya District, Gowa Regency, especially palm farmers, are as follows: (a) The process of collecting palm sap (b) Making palm sugar (c) Marketing (d) Government assistance and support. Second, economic improvement in palm sugar production in Rannaloe Village, Bungaya District, Gowa Regency, especially palm farmers, that palm sugar production generally contributes positively to improving the local economy. Community empowerment through (training, and equipment assistance, as well as development of production and marketing management) is an important factor in improving the quality and quantity of palm sugar production, which ultimately has an impact on increasing community income. The implications of this study are expected to the government, both the village secretary, the hamlet head and welfare (Administration) to play a more active role and facilitate the community in community empowerment through palm sugar production in Rannaloe Village, Bungaya District, Gowa Regency